2003
DOI: 10.3164/jcbn.33.83
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Xanthine Oxidase-Derived Oxygen Free Radicals to the Development of Carbon Tetrachloride-Induced Acute Liver Injury in Rats

Abstract: Summary We examined how oxygen free radicals derived from xanthine oxidase (XOD) contribute to the development of carbon tetrachloride (CCl4)-induced acute liver injury in rats. In rats treated with CCl4 (1 ml/kg), liver injury appeared 3 h after the treatment and developed by 24 h, judged from the serum levels of transaminases. Hepatic and serum XOD activities and serum uric acid concentration did not change 6 h after CCl4 treatment, but they all increased at 12 h and further increased at 24 h. An increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 45 publications
9
27
0
Order By: Relevance
“…Hepatic XO activity in CCl4-treated rats increased 24 h after the toxicant treatment. These time-related changes observed in the liver of CCl4-treated rats were well consistent with those reported previously [9,13,14]. We have reported that XO-derived ROS contributes to stimulation of hepatic lipid peroxidation and disruption of hepatic antioxidant defense systems at a progressed stage of CCl4-induced acute liver injury in rats [13].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Hepatic XO activity in CCl4-treated rats increased 24 h after the toxicant treatment. These time-related changes observed in the liver of CCl4-treated rats were well consistent with those reported previously [9,13,14]. We have reported that XO-derived ROS contributes to stimulation of hepatic lipid peroxidation and disruption of hepatic antioxidant defense systems at a progressed stage of CCl4-induced acute liver injury in rats [13].…”
Section: Discussionsupporting
confidence: 80%
“…Rats received a single i.p. injection of CCl4 at a dose of 1 ml/kg body weight as a 50% olive oil solution between 9:00 and 10:00 am, as described previously [9,11,13,14]. The CCl4-untreated rats received an equal volume of olive oil in the same manner.…”
Section: Ccl4 and Tj-15 Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations